The effect of regular exercise and vitamin C on hs-cTnT TNF-α levels in obese boys students - Mohammadbagher Forghani Ozrudı; Javad Alızade; Aliakbar Raıespour (Türk Spor ve Egzersiz Dergisi)
This study aimed to determine the effect of regular exercise and vitamin C on hs-cTnT and TNF-α levels in obese boys Students. In this regard, 28 Students aged 10-13 years, targeted sampling and available, were randomly divided into control, exercise, supplementation, exercise + supplement. The training protocol for group exercise and submaximal aerobic exercise + supplement includes eight weeks of growing at 50 to 70 percent of maximum heart rate, core exercise 30 to 45 minutes per session, 3 sessions per week. Also, subjects in the exercise group and exercise + supplement tablets of vitamin C (500 mg) after taking food, ate every other day for 8 weeks. Blood samples were collected after 12 hours of fasting in pre-test and post-test (48 hours after the last exercise). Serum levels of hs-cTnT and TNF-α by Electro-Chemiluminescence and ELISA (respectively) were measured. The results showed that 8 weeks of aerobic exercise, vitamin C and combination of the above interventions have an impact on hs-cTnT levels in obese boy’s students, but TNF-α levels decreased significantly. Furthermore, the effect on the reduction of TNF-α combined intervention of vitamin C was significantly higher. Therefore the use of non-pharmacological methods, exercise, vitamin C and combination of the above interventions may lead to a reduction of inflammation in obese boy’s students.